Improving Students’ Writing Skill In Recount Text Using Wordless Picture Book Of Grade X At Al-Washliyah Petumbukan Academic Year 2023/2024 - Windari Sembiring; Wiki Tedi Rahmawati; Syafrina Prihatini (Journal on Education, 2024)
Based on the results of observations made in class X SMA Alwashliyah Petumbukan, it can be seen that the ability of students to write in a recount text, students still difficulty in making sentences in English because of the lack of was still low vocabulary, they have difficulty in developing their ideas into writing because of the lack of media. Based on the background in this research, this research aimed to improve the writing skill of recount text of grade X students by using wordless picture book. This type of research was Classroom Action Research (CAR) which consists of 4 stages, namely planning, action, observation and reflection. The subjects of this study were X grade students of SMA Alwashliyah Petumbukan in the academic year 2023/2024, totaling 19 students including 5 men and 14 women. Data collection used 2 ways, namely quantitative and qualitative data. Quantitative data collection using the results of students’ writing recount text in pre-test, post-test 1 and post-test II, while qualitative data collection used the results of observations, field notes and interviews.The results of the study stated that the use of Wordless Picture Book media can improve students' writing skills.It can be seen that there was significant increase from cycle 1 to cycle 2. The average score obtained from post-test I was 67.11 with a passing percentage of 37%. Furthermore, in cycle 2 the average student score was 82.89 with a passing percentage of 89%. This showed that using wordless picture book can improve students' skill in writing recount text and this research was successful.